Strategi Promosi Perkreditan Pada PT. BPR Yaspis Dana Prima Tentena Kecamatan Pamona Puselemba Kabupaten Poso - Yulia Angelina Posumah; Fredrik Bastian Kawani; Marthen Sangkide (Interdisciplinary Journal (IDe), 2023)
The purpose of this study is to determine the Credit Promotion Strategy at PT. BPR Yaspis Dana Prima Tentena, Pamona Puselemba District, Poso Regency. The research approach is carried out in a qualitative descriptive manner, namely collecting, processing and explaining data regarding the promotional strategies implemented by PT. BPR Yaspis Dana Prima Tentena so that the data can be a clear and easy to understand information. This study was conducted for two months, the data collected by researchers was in the form of primary data and secondary data using data collection techniques through observation, interviews and documentation. In-depth interviews were conducted with eight key informants. The results showed that the promotional strategy that had been implemented got results, namely an increase in the amount of credit given. This proves that policies for customers who have non-performing loans can be overcome properly, with customer awareness to fulfill their obligations. The number of customers has not increased not because the promotional strategy is not working well, but because the Covid-19 Pandemic has made lending unworkable for business actors whose businesses have experienced the impact of the Covid-19 Pandemic. If the restructuring relaxation period has been completed, PT. BPR Yaspis Dana Prima Tentena will re-evaluate the company's performance system, one of which is regarding promotion strategies in increasing the number of customers.